Superhydrophobic surfaces as a source of airborne singlet oxygen through free space for photodynamic therapy - Aebisher, David (2020)
A superhydrophobic (SH) sandwich system has been developed to enable "contact-free" airborne singlet oxygen (1O2) delivery to a water droplet. The contact-free feature means that the sensitizer is physically separated from the droplet, which presents opportunities for photodynamic therapy (PDT). Trapping of airborne 1O2 in a H2O droplet residing on a lower SH surface was monitored with 9,10-anthracene dipropionate dianion by varying distances to an upper 1O2-generating surface. Short distances of 20 μm efficiently delivered airborne 1O2 to the droplet in single-digit picomolar steady-state concentrations. Delivery decreases linearly with distance, but 50% of the 1O2 steady-state concentration is trapped at a distance of 300 μm from the generating surface. The 1270 nm luminescence intensity was measured within the SH sandwich system, confirming the presence of airborne 1O2. Physical quenching of 1O2 to ground-state 3O2 by the water droplet itself and both physical and chemical quenching of 1O2 by the water droplet containing the trap 9,10-anthracene dipropionate dianion are observed. Unlike a majority of work in the field of PDT with dissolved sensitizers, where 1O2 diffuses short (hundreds of nanometers) distances, we show the delivery of airborne 1O2 via a superhydrophobic surface is effective through air in tenths of millimeters distances to oxidize an organic compound in water. Our results provide not only potential relevance to PDT but also surface bacterial inactivation processes.